Improving Students Writing Anecdote Skill Through Scientific Method In The First Grade Students Of SMAN 3 Praya - Yulandari, Evi Safitri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
This study was aimed to know the writing anecdote skill in the first grade students of SMAN 3 Praya, the researcher chose the anecdote as the material because there are 13 kind of text in English, but anecdote is rarely taught by the teacher whereas anecdote is interesting story about a real incident or person and the students may interested when they learn about anecdote text. This research used scientific method, The term “Scientific Method” gained its popularity in the field of education in Indonesia when Curriculum 2013 was launched by Ministry of Education and Culture in 2013, It is explicitly stated in the curriculum that, with its excellences, the scientific method is very important for a better quality of teaching and learning to develop students’ affection, knowledge, and skills. The researcher did a qualitative case study with the total 30 students’ involved as well as participant. This study used several data instrument in gathering the data dealing with the question of the study, i.e: observation, interview and questionnaire form to collect the data in a case study to explore (1.) whether or not the teacher is able to implement scientific method to teach writing anecdote skill; (2) how the teacher interprets scientific method; (3) the students’ perception toward anecdote text and scientific based learning activity. This research might be the window for further studies or reference to explore the potential benefit and challenge of scientific method in teaching writing anecdote text, particularly for senior high school level.